Regret and Other Emotions Related to Decision-Making: Antecedents, Appraisals, and Phenomenological Aspects - Matarazzo, Olimpia; Abbamonte, Lucia; Greco, Claudia; Pizzini, Barbara; Nigro, Giovanna (Frontiers in Psychology, 2021)
Abstract: Objectives: The mainstream position on regret in psychological literature is that its necessary conditions are agency and responsibility, i.e. to choose freely but badly. Without free choice, other emotions, such as disappointment, are deemed to be elicited when the outcome is worse than expected. In two experiments, we tested the opposite hypothesis that being forced by external circumstances to choose an option inconsistent with one’s own intentions is an important source of regret and a core component of its phenomenology, regardless of the positivity/negativity of the post-decision outcome. Along with regret, four post-decision emotions - anger towards oneself, disappointment, anger towards circumstances, satisfaction - were investigated to examine their analogies and differences to regret with regard to antecedents, appraisal and phenomenological aspects. Methods: Through the scenario methodology, we manipulated three variables: choice (free/forced), outcome (positive/negative), time (short/long time after decision making). Moreover, we investigated whether responsibility, decision justifiability, and some phenomenological aspects (self-attribution, other-attribution and contentment) mediated the effect exerted by choice, singularly or in interaction with outcome and time, on the five emotions. Each study was conducted with 336 participants, aged 18-60. Results: The results of both studies were similar and supported our hypothesis. In particular, regret elicited by forced choice was always high, regardless of the valence of outcome, whereas free-choice elicited regret was high only with a negative outcome. Moreover, regret was unaffected by responsibility and decision justifiability, whereas it was affected by the three phenomenological dimensions. Conclusions: Our results suggest that the prevailing theory of regret is too binding, since it posits as necessary some requirements which are not; the antecedents and phenomenology of regret are broader than it is generally believed; decision making produces a complex emotional constellation, where the different emotions, singularly and/or in combination, constitute the affective responses to the different aspects of decision making.